Loose Leaf Lettuce Quality Grown in Two Production Systems - Luis L. Travieso; Adrian P. Leon; Veronica R. Logegaray; Diana Frezza; Angel Chiesa (European Scientific Journal, ESJ, 2016)
Horticultural crops have a strong impact on human nutrition. Lettuce is the most important leafy vegetable in Argentina and it is cultivated mainly in green belts, in greenhouses or open field. The aim of this study was to evaluate growth and phytonutrients concentration of leaf lettuce under greenhouse and field production. Crop establishment was made from seedlings produced in a commercial greenhouse. Loose lettuce cv. Brisa was used for field and greenhouse growth. Experimental design with complete random block with 4 replicates per treatment was used. Fresh and dry weights of shoot, number of leaves, color, ascorbic acid, chlorophyll content were measured. Absolute and relative growth rate and commercial yield were calculated. Lettuce grown under greenhouse system showed, as expected, a higher value of fresh and dry weight, number of leaves, leaf area, yield and absolute and relative growth rate. Ascorbic acid value of the leaves decreased during lettuce growth in both production systems. Chlorophyll content was higher in the greenhouse cultivation but the antioxidant capacity was lower in lettuce leaves from greenhouse than the leaves grown on open field.